INCREASE IN SENSITIVITY OF PHOTOELECTRON MULTIPLIER (PHEM) - Pereversentsev, A. F.; Komarov, N. S.; Kantsen, L. E.; Ryabov, A. V.; Lisova, L. E.; Cherkas, A. Y. (Одеські астрономічні публікації, 2017)
Plots of spectral sensitivity as a function of voltage are obtained. A conclusion can be made on the spectral sensitivity shift with voltage increase towards longwave spectrum region.